STRATEGI PENGEMBANGAN INOVASI PRODUK BERBASIS PISANG PADA BEBERAPA UKM DI KOTA BATURAJA (JASEP, 2018)
This research is a strategy of development of banana based product innovation on some ukm in baturaja city this research method use survie disproportionate stratified random sampling result of this research is Based on research which have been done, hence can be concluded that Strategy of Banana Product Innovation Development In Baturaja City Ogan Komering Ulu Regency are as follows: Strategy (SO) Business expansion by utilizing borrowed funds from financial institutions or SOEs with low interest rates, expanding the distributor network and channeling products to areas that have never been entered, increasing the number of production of banana based products, Strategy (ST) Maintaining the quality of banana-based products, maintaining the production of banana-based products, increasing the supply of raw materials, Strategy (WO) Must improve tools and technology better, and need to promote product and Strategy (WT),Keyword: